Using rhetorical structure theory in Automatic Text Summarization for Marcu-Authored Documents - Borra, Allan; Diola, Almira Mae.; Ong Lopez, Joan Tiffany T.; Torralba, Phoebus Ferdiel; So, Sherwin
An automatic text summarizer system using Rhetorical Structure Theory (RST) is a formalism developed by Mann and Thompson (1988) that allows for discourse analysis of multi-sentence text...
Issued also online.
Keywords: Automatic text summarization; Natural language processing .; Keyword extraction; Rhetorical structure theory